Building religious, honesty, discipline and student curiosity characters in online HOTS-based citizenship education learning - Chotimah, Umi; Kurnisar, Kurnisar; Ermanovida, Ermanovida; Juainah, Norma (Universitas Negeri Yogyakarta, 2021)
This article aims to describe the efforts to build religious, honesty, discipline, and student